The danger of feeling fine: Objective–subjective thermal mismatch in delivery workers under urban heat extremes - Hanhui Yu; Shen Yang; Sai Liu; Lanfei Jiang; Chen Zhong; Junqi Wang (Sustainable Cities and Society, 2026)

Electrochemical reconstruction of CoP/CuP2 into cobalt-defect-enriched catalyst for enhanced methanol oxidation reaction - Gehua Yu; Yihan Huang; Tianming Li; Hanhui Zeng; Hefei Feng; Yuanbin Zheng; Junhao Pan; Jiahui Chen; Xian-Zhu Fu (Fuel, 2026)

The hidden risk in high-temperature urban environments: assessment of metal elements and human health risks of particulate matter at street - Zixuan Li; Lanfei Jiang; Hanhui Yu; Junqi Wang (Journal of Hazardous Materials, 2025)

Mechanisms and characteristics of sand seepage deformation under groundwater level fluctuation scenarios - Yu Fan; Kun Huang; Junwei Wan; Hanhui Wen; Jincai Qu; Longxuan Zhang (Journal of Hydrology, 2025)

Zonal demand-controlled ventilation strategy to minimize infection probability and energy consumption: A coordinated control based on occupant detection - Chen Ren; Hanhui Yu; Junqi Wang; Hao-Cheng Zhu; Zhuangbo Feng; Shi-Jie Cao (Environmental Pollution, 2024)

Intelligent ventilation control in enclosed environment towards health and energy efficiency: A study of elevator cabins - Junqi Wang; Hanhui Yu; Nuodi Fu; Zhuangbo Feng; Congpei Li (Energy and Buildings, 2023)

Non-vernalization requirement in Chinese kale caused by loss of BoFLC and low expressions of its paralogs - Qiwei Tang; Hanhui Kuang; Changchun Yu; Guanghui An; Rong Tao; Weiyi Zhang; Yue Jia (Theoretical and Applied Genetics, 2022)
Key message We identified the loss of BoFLC gene as the cause of non-vernalization requirement in B. oleracea . Our developed codominant marker of BoFLC gene can be used for breeding program of B. oleracea crops . Abstract Many species of the Brassicaceae family, including some Brassica crops, require vernalization to avoid pre-winter flowering. Vernalization is an unfavorable trait for Chinese kale ( Brassica oleracea var. chinensis Lei ), a stem vegetable, and therefore it has been lost during its domestication/breeding process. To reveal the genetics of vernalization variation, we constructed an F 2 population through crossing a Chinese kale (a non-vernalization crop) with a kale (a vernalization crop). Using bulked segregant analysis (BSA) and RNA-seq, we identified one major quantitative trait locus (QTL) controlling vernalization and fine-mapped it to a region spanning 80 kb. Synteny analysis and PCR-based sequencing results revealed that compared to that of the kale parent, the candidate region of the Chinese kale parent lost a 9,325-bp fragment containing FLC homolog ( BoFLC ). In addition to the BoFLC gene, there are four other FLC homologs in the genome of B. oleracea , including Bo3g005470 , Bo3g024250 , Bo9g173370, and Bo9g173400 . The qPCR analysis showed that the BoFLC had the highest expression among the five members of the FLC family. Considering the low expression levels of the four paralogs of BoFLC , we speculate that its paralogs cannot compensate the function of the lost BoFLC, therefore the presence/absence (PA) polymorphism of BoFLC determines the vernalization variation. Based on the PA polymorphism of BoFLC , we designed a codominant marker for the vernalization trait, which can be used for breeding programs of B. oleracea crops.